Descriptions of Macrolygistopterus subparallelus Pic, 1930 immatures from southeastern Brazil (Coleoptera, Lycidae, Lycinae, Calochromini) - Costa, Cleide; Vanin, Sergio A. (Zootaxa, 2012)
Mature larva and pupa of Macrolygistopterus subparallelus Pic are described and compared to known Calochromini im-matures. Larvae were collected alive inside dead trunk in the Atlantic Forest at Estação Biológica de Boracéia, Salesópo-lis, São Paulo, Brazil. They were maintained in laboratory conditions, and the pupal period was 12 days (one observation).The pupa of this genus is described for the first time. This larva differs from known Calochromini larvae mainly because of its almost cylindrical campodeiform body and longer urogomphi.